1999
DOI: 10.1212/wnl.52.9.1876
|View full text |Cite
|
Sign up to set email alerts
|

Familial aggregation of Parkinson’s disease

Abstract: In this large sample of prevalent PD patients and population-matched controls, PD significantly aggregates in families, with the strength of the association being age-dependent. Therefore, familial factors, which can be genetic, environmental, or both, play a role in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
93
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 31 publications
12
93
2
Order By: Relevance
“…A recent large population-based case-control study found that PD significantly aggregated in families, the strength of the association being age-dependent. This is in keeping with the fact that familial factors, which can be genetic, environmental, or both, play a role in PD (Elbaz et al 1998). Overall, the relative risk in first degree relatives of probands with PD is in the range of 2-3, which is similar to that found in AD (Farrer et al 1989).…”
Section: Epidemiological Studiessupporting
confidence: 78%
“…A recent large population-based case-control study found that PD significantly aggregated in families, the strength of the association being age-dependent. This is in keeping with the fact that familial factors, which can be genetic, environmental, or both, play a role in PD (Elbaz et al 1998). Overall, the relative risk in first degree relatives of probands with PD is in the range of 2-3, which is similar to that found in AD (Farrer et al 1989).…”
Section: Epidemiological Studiessupporting
confidence: 78%
“…This study joins several others finding sporadic PD subjects more commonly report positive PD family histories than control subjects [23,[25][26][27][28][29][30][31][32]. Perhaps PD itself increases ones awareness of PD or parkinsonism in others, or control status reduces awareness, rendering in either case a secondary artifact [33].…”
Section: Discussionsupporting
confidence: 82%
“…The genetic hypothesis is supported by community-based studies showing that a substantial number of PD patients have similarly affected relatives. 3,4 This was also revealed by a PD study conducted by us on Crete, 5 an island of about 0.6 million people sharing the same genetic and cultural background and a common environment. Moreover, this study suggested an oligogenic model for PD, according to which disease-predisposing alleles from two or more genes need to be present in the same individual for the disorder to be expressed.…”
Section: Introductionmentioning
confidence: 68%